Analysis of Sharia Financial Management at The Finance Bureau And Bustanul Ulum Mlokorejo Business Entity - Siti Nur Haliza; M. Fikri Syaifulloh; M. Wasil (Yayasan Dinamika Ilmu Banyuwangi, 2025)
This study aims to analyze the implementation of sharia financial management at the Finance Bureau and Business Entity (BKBU) of Bustanul Ulum Mlokorejo Islamic Boarding School. As a religiousbased educational institution, the application of sharia principles in financial management is essential to ensure accountability, transparency, and operational sustainability. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, direct observations, and documentation. The informants consisted of BKBU management and service users, particularly those involved in KBIHU (Hajj and Umrah Guidance Group) activities. Data validity was ensured through source and technique triangulation. The findings indicate that BKBU has implemented sharia financial management principles, including the prohibition of riba, and the application of honesty (ṣidq), trustworthiness (amānah), and transparency in financial recording and reporting. Financial management is carried out through systematic stages, including planning, implementation, supervision, and evaluation. The institution demonstrates both technical and allocative efficiency, although limitations in resources still affect optimal fund distribution in certain programs. Furthermore, periodic financial reporting and stakeholder involvement contribute to strengthening institutional accountability. This study contributes to the discourse on Islamic financial management in educational institutions by providing empirical evidence that the integration of sharia principles with modern management practices enhances financial governance. It also highlights the importance of human resource competence, administrative systems, and the adoption of simple digital tools in supporting effect